High speed chalcogenide glass electrochemical metallization cells with various active metals. (1st June 2018) - Hughes, Mark A; Burgess, Alexander; Hinder, Steven; Gholizadeh, A Baset; Craig, Christopher; Hewak, Daniel W
Abstract: We fabricated electrochemical metallization cells using a GaLaSO solid electrolyte, an InSnO inactive electrode and active electrodes consisting of various metals (Cu, Ag, Fe, Cu, Mo, Al). Devices with Ag and Cu active metals showed consistent and repeatable resistive switching behaviour, and had a retention of 3 and >43 days, respectively; both had switching speeds of <5 ns. Devices with Cr and Fe active metals displayed incomplete or intermittent resistive switching, and devices with Mo and Al active electrodes displayed no resistive switching ability. Deeper penetration of the active metal into the GaLaSO layer resulted in greater resistive switching ability of the cell. The off-state resistivity was greater for more reactive active metals which may be due to a thicker intermediate layer.